Genetic engineering of dinoflagellate algae and the lethality of an introduced plastid terminal oxidase - I.C. Nimmo; C.E. Evans; L.M. Li; A.C. Barbrook; K. Geisler; F.H. Kleiner; A. Scarampi; D. Kosmützky; L.T. Wey; R.G. Dorrell; C.J. Howe; R.E.R. Nisbet (Protist, 2026)

Human-induced trait shifts reshape predator–prey interactions - Eamonn I.F. Wooster; Chris J. Jolly; Dale G. Nimmo; Ben J. Ashton; Mauricio Cantor; Martin J. Whiting; R. Keller Kopf; Simone Des Roches; Alexandra J.R. Carthey; Lauren A. Stanton; Euan G. Ritchie; Michael G. Bertram; et al. (Trends in Ecology & Evolution, 2026)

A collective trigger for widespread planetesimal formation revealed by accretion ages - James F.J. Bryson; Hannah R. Sanderson; Francis Nimmo; Sanjana Sridhar; Gregory A. Brennecka; Yves Marrocchi; Jason P. Terry (Earth and Planetary Science Letters, 2026)

Can impact-induced heating drive moderately volatile element loss? - Meredith A. Calogero; Francis Nimmo; Remco C. Hin (Earth and Planetary Science Letters, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

‘Megafire’—You May Not Like It, But You Cannot Avoid It - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2025)
Aim The term ‘megafire’ is increasingly used to describe large fires worldwide. We proposed a size‐based definition of megafire—fires exceeding 10,000 ha arising from single or multiple related ignition events. A recent perspective in Global Ecology and Biogeography argues against a size‐based definition of megafire and suggest that the term is too emotive for scientific use. We highlight that many scientific terms originate from common terms. These terms are often defined once they enter the scientific lexicon, enhancing both scientific understanding and public communication. We argue that standardised definitions facilitate better prediction, preparation, and management of fire events. Location Worldwide. Time Period 2022–2023. Methods We conducted an updated structured review of the term ‘megafire’ and its use and definition in the peer‐reviewed scientific literature, collating definitions and descriptions and identifying the criteria frequently invoked to define the term. Results We demonstrate an increase in the use of ‘megafire’ in the scientific literature since our original definition in 2022, with many studies adopting the > 10,000 ha size‐based criterion. Main Conclusions We contend that abandoning the term is neither practical, possible, nor beneficial. Instead, consistent usage underpinned by clear definitions is essential. Adopting a clear, size‐based definition of megafire strengthens clarity and comparability across research and management practices globally. Precision in terminology is crucial for advancing research, improving communication, and informing effective fire management and policy.

Did the terrestrial planets of the solar system form by pebble accretion? - A. Morbidelli; T. Kleine; F. Nimmo (Earth and Planetary Science Letters, 2025)

Functional Traits of the World's Late Quaternary Terrestrial Mammalian Predators - Eamonn I. F. Wooster; Erick J. Lundgren; Mairin Balisi; Rhys T. Lemoine; Christopher J. Sandom; Jens‐Christian Svenning; John Rowan; Chris J. Jolly; Grant D. Linley; Mitchell. A. Cowan; Nick Wright; Dylan Westaway; et al. (Global Ecology and Biogeography, 2024)
Motivation Terrestrial predators play key roles in cycling nutrients, as well as limiting prey populations, and shaping the behaviour of their prey. Prehistoric, historic and ongoing declines of the world's predators have reshaped terrestrial ecosystems and are a topic of conservation concern. However, the availability of ecologically relevant predator functional traits is limited, hampering efforts to understand macroecological changes in this ecologically important functional group. Here, we present CarniTraits , a comprehensive open‐access functional trait database of all late Quaternary (~130,000 ybp) terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Main Types of Variables Contained Mammalian terrestrial predator functional traits including body mass, diet, scavenging, locomotion, cooperative hunting, hunting habitat, hunting method, bone consumption, temporal activity patterns, brain mass and encephalisation quotient. Spatial Location and Grain Global. Time Period and Grain Late Quaternary (the last ~130,000 years). Major Taxa and Level of Measurement All late Quaternary terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Software Format csv.

Magnetization and age of ca. 544 Ma syenite, eastern Canada: Evidence for renewal of the geodynamo - Tinghong Zhou; Mauricio Ibañez-Mejia; Richard K. Bono; Rory D. Cottrell; Wouter Bleeker; Kenneth P. Kodama; Wentao Huang; Eric G. Blackman; Francis Nimmo; Aleksey V. Smirnov; John A. Tarduno (Earth and Planetary Science Letters, 2024)

Exploring the potential of topsoil pellets to improve native seedling establishment on degraded agricultural land - Thomas P. Munro; Todd E. Erickson; Dale G. Nimmo; Frederick A. Dadzie; Miriam Muñoz-Rojas; Jodi N. Price (Plant and Soil, 2024)
Background and aims Agricultural activities can degrade soils and promote weeds, posing challenges to native species restoration. In agricultural restoration, removing contaminated topsoil is a method designed to reduce elevated soil nutrients caused by fertilisation. This strategy targets weed control by eliminating both aboveground weeds and their soil seed bank before direct seeding. However, it also diminishes native soil seed banks and beneficial soil microbes. We investigated the potential of fresh topsoil pellets containing seeds to improve seedling performance in a degraded grassy woodland where topsoil had been removed. Methods We tested various pellet recipes, including one using commercial ingredients and three with different topsoil proportions (30%, 50%, and 70%). The study was conducted in a degraded grassy woodland in southeastern Australia, where topsoil was removed for restoration. We explored the effect of these pellet varieties on seedling emergence and growth of six native species common in this community, as well as microbial activity in the soil surrounding the seedlings. Results Pellets significantly improved the emergence of Chrysocephalum apiculatum , providing evidence of their effectiveness. However, pellets significantly reduced Arthropodium milleflorum and Glycine tabacina emergence. Linum marginale and Rytidosperma caespitosum emergence remained unaffected by pellets . One species, Bothriochloa macra, had insufficient emergence for analysis. The microbial activity of the soil surrounding Rytidosperma caespitosum seedlings was significantly improved by pellets, with no significant effects observed for other species. Conclusion Our results demonstrate that topsoil pellets improved the emergence of one native species, but reduced emergence for two others, indicating species-specific responses to pelleting.

Indigenous pyrodiversity promotes plant diversity - L. Greenwood; R. Bliege Bird; C. McGuire; N. Jadai; J. Price; A. Skroblin; S. van Leeuwen; D. Nimmo (Biological Conservation, 2024)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Identifying historical and future global change drivers that place species recovery at risk - William L. Geary; Ayesha I. T. Tulloch; Euan G. Ritchie; Tim S. Doherty; Dale G. Nimmo; Marika A. Maxwell; Adrian F. Wayne (Global Change Biology, 2023)
Ecosystem management in the face of global change requires understanding how co‐occurring threats affect species and communities. Such an understanding allows for effective management strategies to be identified and implemented. An important component of this is differentiating between factors that are within (e.g. invasive predators) or outside (e.g. drought, large wildfires) of a local manager's control. In the global biodiversity hotspot of south‐western Australia, small‐ and medium‐sized mammal species are severely affected by anthropogenic threats and environmental disturbances, including invasive predators, fire, and declining rainfall. However, the relative importance of different drivers has not been quantified. We used data from a long‐term monitoring program to fit Bayesian state‐space models that estimated spatial and temporal changes in the relative abundance of four threatened mammal species: the woylie ( Bettongia penicillata ), chuditch ( Dasyurus geoffroii ), koomal ( Trichosurus vulpecula ) and quenda ( Isoodon fusciventor ). We then use Bayesian structural equation modelling to identify the direct and indirect drivers of population changes, and scenario analysis to forecast population responses to future environmental change. We found that habitat loss or conversion and reduced primary productivity (caused by rainfall declines) had greater effects on species' spatial and temporal population change than the range of fire and invasive predator (the red fox Vulpes vulpes ) management actions observed in the study area. Scenario analysis revealed that a greater extent of severe fire and further rainfall declines predicted under climate change, operating in concert are likely to further reduce the abundance of these species, but may be mitigated partially by invasive predator control. Considering both historical and future drivers of population change is necessary to identify the factors that risk species recovery. Given that both anthropogenic pressures and environmental disturbances can undermine conservation efforts, managers must consider how the relative benefit of conservation actions will be shaped by ongoing global change.

What do you mean, ‘megafire’? - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2022)
Background ‘Megafire’ is an emerging concept commonly used to describe fires that are extreme in terms of size, behaviour, and/or impacts, but the term’s meaning remains ambiguous. Approach We sought to resolve ambiguity surrounding the meaning of ‘megafire’ by conducting a structured review of the use and definition of the term in several languages in the peer‐reviewed scientific literature. We collated definitions and descriptions of megafire and identified criteria frequently invoked to define megafire. We recorded the size and location of megafires and mapped them to reveal global variation in the size of fires described as megafires. Results We identified 109 studies that define the term ‘megafire’ or identify a megafire, with the term first appearing in the peer‐reviewed literature in 2005. Seventy‐one (~65%) of these studies attempted to describe or define the term. There was considerable variability in the criteria used to define megafire, although definitions of megafire based on fire size were most common. Megafire size thresholds varied geographically from > 100–100,000 ha, with fires > 10,000 ha the most common size threshold (41%, 18/44 studies). Definitions of megafire were most common from studies led by authors from North America (52%, 37/71). We recorded 137 instances from 84 studies where fires were reported as megafires, the vast majority (94%, 129/137) of which exceed 10,000 ha in size. Megafires occurred in a range of biomes, but were most frequently described in forested biomes (112/137, 82%), and usually described single ignition fires (59% 81/137). Conclusion As Earth’s climate and ecosystems change, it is important that scientists can communicate trends in the occurrence of larger and more extreme fires with clarity. To overcome ambiguity, we suggest a definition of megafire as fires > 10,000 ha arising from single or multiple related ignition events. We introduce two additional terms – gigafire (> 100,000 ha) and terafire (> 1,000,000 ha) – for fires of an even larger scale than megafires.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Total Water Column Analysis Shows the Importance of a Single Species in Subsurface Chlorophyll Maximum Thin Layers in Stratified Waters - Michelle L. Barnett; Alan E. S. Kemp; W. Alex M. Nimmo-Smith; Duncan A. Purdie (Frontiers in Marine Science, 2022)
Marine phytoplankton form the base of marine food webs and are the driving force of the marine carbon cycle, so understanding the dynamics of their blooms is critical. While near-surface marine productivity (<10 m water depths) is extensively documented, that of the subsurface is less well characterised. Increasing evidence of the importance of subsurface chlorophyll maxima (SCM) and climatically driven increases in stratification of surface waters that promote SCM development call for improved sampling of the subsurface. To address this, we targeted the summer stratified waters of the Western English Channel, part of the NW European shelf seas, where SCM are commonly developed. In situ holography was applied to undertake the highest ever resolution, total water column, quantitative analysis of microplankton distribution, and demonstrated the importance of a SCM, co-located with the thermocline, dominated by a single species, the dinoflagellate Ceratium fusus . This species was dominant in the SCM over a wide area of the NW European shelf in the June/July 2015 study period and comprised up to 85% of the SCM biomass. Analysis of similarity and multivariate non-metric multidimensional scaling showed the phytoplankton community of the SCM to be statistically distinct from those of the surface and deep waters. Holography also revealed a fine scale layering of taxa at different levels within the SCM, likely reflecting ecological differences. Some taxa followed the peak abundance of C. fusus , while others reached maximum abundances immediately below or above the C. fusus maximum, suggesting the possible operation of exclusion mechanisms. Additionally, the detection of abundant aggregates located only within and beneath the SCM demonstrates the potential importance of this deep production for the export of carbon to the sea floor. Some predictions of phytoplankton productivity propose a shift to smaller cells in the more stratified oceans of the future resulting in declining production and export. Results presented here, however, contribute to a growing body of evidence that suggests, on the contrary, that key species among the larger celled/colonial, SCM-adapted diatoms and dinoflagellates may instead be selected in stratified conditions, driving increased production and export.

Constraints on vertebrate range size predict extinction risk - Thomas M. Newsome; Christopher Wolf; Dale G. Nimmo; R. Keller Kopf; Euan G. Ritchie; Felisa A. Smith; William J. Ripple (Global Ecology and Biogeography, 2020)
Aim The only factor in the fossil record that consistently buffers against extinction risk is large geographical range. We ask whether extant vertebrate species with the smallest geographical range for their body size have a higher extinction risk, and thus whether the lower bound of the modern range–body size relationship could serve as an effective conservation prioritization tool. Location Global in scope. Time period Modern. Major taxa studied Six classes of vertebrates. Methods We compiled a database of geographical range, body size and extinction risk for six vertebrate classes ( n = 26,076). We characterized the shape of the relationship between geographical range and body size for each class, using 90% and 10% quantile regression to describe the upper and lower bounds, respectively. We then evaluated the degree of extinction vulnerability of species at the lower bound of the regression using generalized linear mixed models. All analyses accounted for phylogenetic dependence between related species. Results The relationships between species ranges and body sizes were generally positive at both the upper and the lower bounds, and segmented (nonlinear) relationships were common. Despite this variability, species near the lower boundary of the relationship were more often in higher extinction risk categories, and this remained true when the role of range size in the International Union for Conservation of Nature Red Listing criteria was accounted for. Main conclusions Variability in the upper and lower bounds of the range–body size relationship suggests that some classes of vertebrates exhibit combinations of ranges and body sizes that might not reflect historical patterns. Nonetheless, the range–body size relationship remains a reliable and useful predictor of extinction risk, more so than range size does alone. The range–body size relationship could therefore be used to track the trajectories of species towards or away from an extinction threshold and allow the tracking of how different human activities alter the range–body size relationship.

Persistence through tough times: fixed and shifting refuges in threatened species conservation - April E. Reside; Natalie J. Briscoe; Chris R. Dickman; Aaron C. Greenville; Bronwyn A. Hradsky; Salit Kark; Michael R. Kearney; Alex S. Kutt; Dale G. Nimmo; Chris R. Pavey; John L. Read; Euan G. Ritchie; et al. (Biodiversity and Conservation, 2019)

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

Satellite cell response to concurrent resistance exercise and high-intensity interval training in sedentary, overweight/obese, middle-aged individuals - Jamie K. Pugh; Steve H. Faulkner; Mark C. Turner; Myra A. Nimmo (European Journal of Applied Physiology, 2018)

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

The detection and measurement of interleukin-6 in venous and capillary blood samples, and in sweat collected at rest and during exercise - Steve H. Faulkner; Kate L. Spilsbury; James Harvey; Andrew Jackson; Jingfeng Huang; Mark Platt; Alfred Tok; Myra A. Nimmo (European Journal of Applied Physiology, 2014)

The impact of high-intensity intermittent exercise on resting metabolic rate in healthy males - Benjamin Kelly; James A. King; Jonas Goerlach; Myra A. Nimmo (European Journal of Applied Physiology, 2013)

Continental‐Scale Governance and the Hastening of Loss of Australia's Biodiversity - Euan G. Ritchie; Corey J. A. Bradshaw; Chris R. Dickman; Richard Hobbs; Christopher N. Johnson; Emma L. Johnston; William F. Laurance; David Lindenmayer; Michael A. McCarthy; Dale G. Nimmo; Hugh H. Possingham; Robert L. Pressey; et al. (Conservation Biology, 2013)

An Alternative Process Model of Preferential Contaminant Travel Times in the Unsaturated Zone: Application to Rainier Mesa and Shoshone Mountain, Nevada - Brian A. Ebel; John R. Nimmo (Environmental Modeling & Assessment, 2013)

Fire Mosaics and Reptile Conservation in a Fire‐Prone Region - D. G. NIMMO; L. T. KELLY; L. M. SPENCE‐BAILEY; S. J. WATSON; R. S. TAYLOR; M. F. CLARKE; A. F. BENNETT (Conservation Biology, 2013)
Fire influences the distribution of fauna in terrestrial biomes throughout the world. Use of fire to achieve a mosaic of vegetation in different stages of succession after burning (i.e., patch‐mosaic burning) is a dominant conservation practice in many regions. Despite this, knowledge of how the spatial attributes of vegetation mosaics created by fire affect fauna is extremely scarce, and it is unclear what kind of mosaic land managers should aim to achieve. We selected 28 landscapes (each 12.6 km 2 ) that varied in the spatial extent and diversity of vegetation succession after fire in a 104,000 km 2 area in the semiarid region of southeastern Australia. We surveyed for reptiles at 280 sites nested within the 28 landscapes. The landscape‐level occurrence of 9 of the 22 species modeled was associated with the spatial extent of vegetation age classes created by fire. Biogeographic context and the extent of a vegetation type influenced 7 and 4 species, respectively. No species were associated with the diversity of vegetation ages within a landscape. Negative relations between reptile occurrence and both extent of recently burned vegetation (≤10 years postfire, n = 6) and long unburned vegetation (>35 years postfire, n = 4) suggested that a coarse‐grained mosaic of areas (e.g. >1000 ha) of midsuccessional vegetation (11–35 years postfire) may support the fire‐sensitive reptile species we modeled. This age class coincides with a peak in spinifex cover, a keystone structure for reptiles in semiarid and arid Australia. Maintaining over the long term a coarse‐grained mosaic of large areas of midsuccessional vegetation in mallee ecosystems will need to be balanced against the short‐term negative effects of large fires on many reptile species and a documented preference by species from other taxonomic groups, particularly birds, for older vegetation. Mosaicos de Fuego y la Conservación de Reptiles en una Región Propensa al Fuego

Circulating hormone and cytokine response to low-load resistance training with blood flow restriction in older men - Stephen D. Patterson; Melanie Leggate; Myra A. Nimmo; Richard A. Ferguson (European Journal of Applied Physiology, 2013)

Bioaccumulation of Selenium by the Bryophyte Hygrohypnum ochraceum in the Fountain Creek Watershed, Colorado - S. J. Herrmann; J. A. Turner; J. S. Carsella; D. W. Lehmpuhl; D. R. Nimmo (Environmental Management, 2012)

The role of surveillance cultures in the prediction of susceptibility patterns of Gram-negative bacilli in the intensive care unit - H. Baba; G. R. Nimmo; A. M. Allworth; R. J. Boots; Y. Hayashi; J. Lipman; D. L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Methicillin-susceptible, non-multiresistant methicillin-resistant and multiresistant methicillin-resistant Staphylococcus aureus infections: a clinical, epidemiological and microbiological comparative study - W. J. Munckhof; G. R. Nimmo; J. Carney; J. M. Schooneveldt; F. Huygens; J. Inman-Bamber; E. Tong; A. Morton; P. Giffard (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Temperature dependence of soleus H-reflex and M wave in young and older women - Susan Dewhurst; Philip E. Riches; Myra A. Nimmo; Giuseppe De Vito (European Journal of Applied Physiology, 2005)

The reproducibility of closed-pouch sweat collection and thermoregulatory responses to exercise?heat stress - Gavin Hayden; Helen C. Milne; Mark J. Patterson; Myra A. Nimmo (European Journal of Applied Physiology, 2004)

Effects of Excess Copper on Growth of Wild Rice ( Zizania palustris ) Seedlings Tested in Reconstituted and Natural Waters - Del Wayne R. Nimmo; Michael A. Preul; Carla J. Castle; James R. Self; Robert W. Pillsbury; Elizabeth A. Bergey (Environmental Management, 2003)

Partial purification and characterization of a protein inhibitor of phosphoenolpyruvate carboxylase kinase - Gilian A. Nimmo; Malcolm B. Wilkins; Hugh G. Nimmo (Planta, 2001)

Nutrification impacts on coral reefs from northern Bahia, Brazil - O. S. Costa; Z. M. A. N. Leão; M. Nimmo; M. J. Attrill (Hydrobiologia, 2000)

Electromyogram changes during sustained contraction after resistance training in women in their 3rd and 8th decades - Andrea Macaluso; Giuseppe De Vito; Francesco Felici; Myra A. Nimmo (European Journal of Applied Physiology, 2000)

Effects of moderate dietary manipulation on intermittent exercise performance and metabolism in women - N. J. Lynch; S. D. R. Galloway; M. A. Nimmo (European Journal of Applied Physiology, 2000)

Effects of menstrual cycle phase and oral contraceptive use on intermittent exercise - N. J. Lynch; M. A. Nimmo (European Journal of Applied Physiology, 1998)

Toxicity of Aroclor® 1254 and its physiological activity in several estuarine organisms - D. R. Nimmo; D. J. Hansen; J. A. Couch; N. R. Cooley; P. R. Parrish; J. I. Lowe (Archives of Environmental Contamination and Toxicology, 1975)